Crystal plasticity enhances trace element mobility in garnet - Tacchetto, Tom; Reddy, Steven M.; Fougerouse, Denis; Clark, Chris; Saxey, David W.; Rickard, William D.A. (2022)
Chemical heterogeneities along grain boundaries in garnet occur across a wide range of metamorphic conditions, yet the processes underlying their development remain poorly understood. Here we integrate electron backscattered diffraction (EBSD) and atom probe tomography (APT) to evaluate the mechanisms driving nanoscale trace element mobility to deformation microstructures in a granulite-facies garnet. This approach shows that low-angle boundaries can be enriched in Ca, Ti, P, Cu, K, Na, Cl, and H. Based on the correlation between EBSD and APT data, we propose that solute ions (Ca, Ti, P, and Cu) were segregated to the interface during the migration of dislocation associated with ductile deformation of the grain. In contrast, elements such as K, Na, Cl, and H are interpreted to reflect diffusion along the low-angle boundary from an externally derived fluid source. These results provide the missing link between chemical heterogeneity and deformation-related microstructures in garnet. Our approach shows that a combination of microstructural and nanoscale geochemical analyses can provide unprecedented insights into mechanisms of element transfer within minerals.